2020
DOI: 10.1371/journal.pone.0232818
|View full text |Cite
|
Sign up to set email alerts
|

Improving yield and fruit quality traits in sweet passion fruit: Evidence for genotype by environment interaction and selection of promising genotypes

Abstract: Breeding for yield and fruit quality traits in passion fruits is complex due to the polygenic nature of these traits and the existence of genetic correlations among them. Therefore, studies focused on crop management practices and breeding using modern quantitative genetic approaches are still needed, especially for Passiflora alata, an understudied crop, popularly known as the sweet passion fruit. It is highly appreciated for its typical aroma and flavor characteristics. In this study, we aimed to reevaluate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…P10 (breeding germplasm) showed the highest plant yield followed by the variety INIAP 2009, both genotypes have reported good yield [ 5 ] but this trait is influenced by the environment. On the other hand, sweet passion fruit showed low plant yield per plant, which is in agreement with Chavarría-Perez et al [ 26 ] who reported low yields for this species. However, the lowest yield was reached by PICH1 which is a local germplasm that is cultivated by few farmers.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…P10 (breeding germplasm) showed the highest plant yield followed by the variety INIAP 2009, both genotypes have reported good yield [ 5 ] but this trait is influenced by the environment. On the other hand, sweet passion fruit showed low plant yield per plant, which is in agreement with Chavarría-Perez et al [ 26 ] who reported low yields for this species. However, the lowest yield was reached by PICH1 which is a local germplasm that is cultivated by few farmers.…”
Section: Resultssupporting
confidence: 90%
“…In terms of plant vigor, no nutrient deficiency was observed in the field. It may be inferred the passion fruit genotypes INIAP 2009, P10, Criolla POR1, and sweet passion fruit had an adequate vegetative growth since their yields were similar to those reported yields in other studies in Ecuador and Brazil [ 5 , 26 ]. Gulupa showed lower plant yield than that reported by Rodríguez-Polanco et al [ 28 ] in Colombia, and PICH1 had the lowest plant yield.…”
Section: Resultssupporting
confidence: 82%
“…AR1H was the most suitable covariance structure for residual effects. The AR1H covariance structure is often used in spatial analyses, considering that as the distance between two plots increases, the correlation between them decreases (Chavarría‐Perez et al., 2020; Gilmour et al., 1997). This concept can be applied in repeated measures context, i.e., the correlation between two measures decreases as the time between them increases (Piepho & Eckl, 2014; Verbyla et al., 2021; Wolfinger, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These predictions are greater than those of Valente et al [11], who selected ten progenies, managed them in the same area, under the same conditions used in the present study, and reported a mean yield of 763 g•plant −1 , or 847 kg.ha −1 . Plant breeding for yield and quality traits in fruits is complex due to the polygenic nature of these traits and the existence of genetic correlations among them [38][39][40][41].…”
Section: Selection Gains In Sacha-inchi Progeniesmentioning
confidence: 99%